2019
DOI: 10.3762/bjoc.15.145
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of oxiranes with cyclodextrins under high-energy ball-milling conditions

Abstract: This work presents a proof of concept for a green cyclodextrin derivatisation method that uses low-boiling epoxide reagents in a high-energy ball mill (HEBM). The simplified preparation and purification of low substitution-degree common (2-hydroxy)propylated β- and γ-cyclodextrins (β/γ-CDs) has been realised. The intelligent use of propylene oxide has also facilitated the more effective synthesis of highly substituted γ-CD. Epichlorohydrin-crosslinked CD-polymers (CDPs) have also been effectively prepared in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The article mentions that a small amount of water can be used to knead the mixture to prepare a paste solution, which has potential in the treatment of biologically active phenolic compounds, the purification of wastewater or the reuse of agricultural waste. Giancarlo Cravotto et al [ 41 ] used low-boiling epoxy reagents in high-energy ball mills (HEBM) to simplify the preparation and purification of low-substitution (2-hydroxy) propylated β-and γ-cyclodextrins (β/γ-CDs). Compared with traditional methods, the properties of mechanically synthesized pCD, such as the degree of complexation, are different, and most of them are better.…”
Section: Synthesis Of Pcdsmentioning
confidence: 99%
“…The article mentions that a small amount of water can be used to knead the mixture to prepare a paste solution, which has potential in the treatment of biologically active phenolic compounds, the purification of wastewater or the reuse of agricultural waste. Giancarlo Cravotto et al [ 41 ] used low-boiling epoxy reagents in high-energy ball mills (HEBM) to simplify the preparation and purification of low-substitution (2-hydroxy) propylated β-and γ-cyclodextrins (β/γ-CDs). Compared with traditional methods, the properties of mechanically synthesized pCD, such as the degree of complexation, are different, and most of them are better.…”
Section: Synthesis Of Pcdsmentioning
confidence: 99%
“…BM reactions are suitable for the synthesis of SiO 2 /CD composites [91] and chemically stable CD polymers [85,92]. The water and pH more sensitive CD-nanosponge preparations are also an excellent target of the mechanochemical syntheses.…”
Section: Mechanochemical Transformation In Millsmentioning
confidence: 99%
“…Finally, we attempted the ring opening of epoxide using ball milling, a mecanosynthesis technique widely used in green chemistry [12,13]. Very recently, Cravotto et al [14] described ring opening of low-boiling epoxides by CDs under high-energy ball milling conditions and in the presence of NaOH, leading to well-known HP-β-CD, HP-γ-CD and epichlorhydrin cross-linked CD-polymers. We tried to initiate the opening reaction of methyl oleate epoxide by β-CD with various bases and acids in the absence of solvent.…”
Section: Scheme 1 Epoxidation Reaction Of Methyl Oleatementioning
confidence: 99%
“…Indeed, activation modes such as ultrasound [8,9], microwaves [10,11], or mechanochemistry [12] are considered as useful green tools for the chemical modification of cyclodextrins. Cravotto et al reported some works where ball milling is used to obtain well-known CD derivatives but under green and solventless conditions and with better yields [13,14]. Very few examples of more specific regioselectivity induced by mechanochemistry are reported.…”
Section: Introductionmentioning
confidence: 99%